2015
DOI: 10.4269/ajtmh.14-0478
|View full text |Cite
|
Sign up to set email alerts
|

Neuritis and Gastrointestinal Hemorrhage in Scrub Typhus Patients

Abstract: Abstract.A 78-year-old woman with scrub typhus exhibited gastric hemorrhage with multiple gastric ulcers. This is the first report to confirm pathologically the presence of not only vasculitis but also, neuritis. The results suggest the necessity of studies confirming neuritis as the cause of gastric ulcer and bleeding in scrub typhus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…A recent report involving hematoxylin‐eosin staining and immunohistochemical staining of samples from patients with hemorrhagic ulcers caused by scrub typhus confirmed that the main pathogenesis of scrub typhus involves neuritis as well as vasculitis. Moreover, in some cases, hemorrhage was found to aggravate due to neuritis‐induced failure in the nerve defense mechanism . However, in our patients, the prevalence of hemorrhage was significantly lower in the OT‐PU group than in the HP‐PU group (26 of 79, 32.9% vs 8 of 62, 12.9%; P = .007).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…A recent report involving hematoxylin‐eosin staining and immunohistochemical staining of samples from patients with hemorrhagic ulcers caused by scrub typhus confirmed that the main pathogenesis of scrub typhus involves neuritis as well as vasculitis. Moreover, in some cases, hemorrhage was found to aggravate due to neuritis‐induced failure in the nerve defense mechanism . However, in our patients, the prevalence of hemorrhage was significantly lower in the OT‐PU group than in the HP‐PU group (26 of 79, 32.9% vs 8 of 62, 12.9%; P = .007).…”
Section: Discussioncontrasting
confidence: 49%
“…It can be speculated that direct involvement of systemic vasculitis leads to gastrointestinal symptoms and signs . Scrub typhus ulcer is characterized by acute inflammatory cell infiltration and thrombus in small vessel, which is considered characteristic feature of vasculitis . It need more study on comparison of pathogenetic mechanisms and pathology between H. pyroli ulcer and scrub typhus ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…2E) and may indicate that the upregulation of ALT and AMY might be highly dependent on IFN-γ stimulation. Dehydration may also manifest in severely infected mice, as evidenced by elevated minerals in the blood attributed to gastrointestinal dysfunction, akin to observations in patients[57, 58].…”
Section: Discussionmentioning
confidence: 94%
“…This is not consistent with the histological result which shows extensive necrosis in the absence of IFN-γ signaling (Fig 2E ) and may indicate that the upregulation of ALT and AMY might be highly dependent on IFN-γ stimulation. Dehydration may also manifest in severely infected mice, as evidenced by elevated minerals in the blood attributed to gastrointestinal dysfunction, akin to observations in patients [61,62].…”
Section: Plos Pathogensmentioning
confidence: 87%